A clinical randomized controlled trial: moxibustion at Laogong interval with Panax notoginseng promoted the maturation of arteriovenous fistulae - Yurou Chen; Lin Xu; Di Huang; Dongping Chen; Feng Wu; Luobing Wang; Jie Zhou; Tianying Lan; Xuehua Qin; Chaoyang Ye (BMC, 2022)
Abstract Background We aim to study the clinical effect of moxibustion at Laogong interval with Panax notoginseng on the short-term maturation and long-term patency of arteriovenous fistula. Methods Seventy-four pre-dialysis uremic patients who received distal forearm radial-cephalic fistula creations were enrolled in this study and randomly assigned to the control group and experimental group. After arteriovenous fistula creations, the control group underwent handgrip exercise, and the experimental group received moxibustion at Laogong acupoint interval with Panax notoginseng. Both groups received a 12-week treatment and were followed up for 24 weeks in all at the following time points: before creations and 2, 4, 8, 12, 24 weeks after creations. The diameter of anastomosis, the diameter and outflow of draining-veins 5 cm above anastomosis, the diameter and outflow of brachial arteries evaluated the maturation and patency of arteriovenous fistula. Enzyme linked immunosorbent assay determined serum levels of endothelin and nitric oxide. Results The maturity rate in the experimental group was significantly higher than that in the control group at 4 weeks after arteriovenous fistula creations (P = 0.048). The diameter of anastomosis, the diameter of draining veins, and the blood flow of draining veins increased in both groups during the whole 24 weeks. The diameter and blood flow of brachial arteries ascended in both groups during the previous 12 weeks. Compared with the control group, moxibustion at Laogong interval with Panax notoginseng significantly improved the value of the diameter of draining-veins (P = 0.016), the blood flow of draining-veins (P = 0.015), the diameter of brachial arteries (P < 0.001), and the blood flow of brachial arteries (P = 0. 012) at 2 weeks, and enhanced the blood flow of draining-veins (P = 0.029) and brachial arteries (P < 0.001) at 12 weeks. Serum levels of endothelin were significantly lower (P = 0.047), and serum levels of nitric oxide were markedly higher (P < 0.001) in the experimental group than that in the control group at 2 weeks after creations. Conclusions Moxibustion at Laogong interval with Panax notoginseng was non-invasive and promoted the maturation of arteriovenous fistula at 4 weeks after creations. However, its long-term beneficial effect on patency at 24 weeks after creations was not significant. Trial registration Chinese Clinical Trial Registry, No. ChiCTR1900024042. Registered, http://www.chictr.org.cn/index.aspx